Paradigm and Strategies for Enhancing Zakat Collection through Collaboration - Razi Azwar Syahbuddin Dalimunthe; Rosnani Siregar (International Tatho Academics, 2026)
The focus of this qualitative research in the form of a case study is to describe the paradigm and strategies for improving zakat collection through strengthening collaboration between the Zakat Collection Unit and the Regional Government in North Padang Lawas Regency. Data were obtained from lecture materials, discussions, interviews, observations, and Focus Group Discussions (FGD) involving BAZNAS, Mosque Councils, BKMT, village officials, business actors, and government institutions. The results of the study show a significant increase in public zakat literacy, identification of zakat potential in the agricultural, trade, and professional sectors, as well as increased public awareness to channel zakat through official institutions. This research provides strategic contributions to the improvement of zakat governance while highlighting the role of students as agents of change. It is hoped that this program can become a model that can be replicated for sustainable community empowerment based on zakat in other regions